Developmental Origins of Metaflammation; A Bridge to the Future Between the DOHaD Theory and Evolutionary Biology - Itoh, Hiroaki; Ueda, Megumi; Suzuki, Misako; Kohmura-Kobayashi, Yukiko (Frontiers in Endocrinology, 2022)
Metabolic syndrome refers to obesity-associated metabolic disorders that increase the risk of type 2 diabetes, coronary diseases, stroke, and other disabilities. Environmental imbalance during the early developmental period affects health and increases susceptibility to non-communicable diseases, including metabolic syndrome, in later life; therefore, the Developmental Origins of Health and Disease (DOHaD) theory was established. According to the DOHaD theory, the hypothesis of the energy-saving ‘Thrifty Phenotype’ in undernourished fetuses is one of the well-accepted schemes as a risk of developing metabolic syndrome. This phenotype is evolutionarily advantageous for survival of the fittest in a hangry environment after birth, a strong selection pressure, but increases the risk of developing metabolic syndrome under an obesogenic diet according to the ‘Mismatch’ hypothesis. Increasing evidences support that chronic inflammation pathophysiologically connects obesity to metabolic disorders in metabolic syndrome, leading to the concept of ‘Metaflammation’. ‘Metaflammation’ in humans is proposed to originate from the evolutionary conservation of crosstalk between immune and metabolic pathways; however, few studies have investigated the contribution of evolutionary maladaptation to the pathophysiology of ‘Metaflammation’. Therefore, it is promising to investigate ‘Metaflammation’ from the viewpoint of selective advantages and its ‘Mismatch’ to an unexpected environment in contemporary lifestyles, in consideration of the principal concept of evolutionarily conserved nutrient sensing and immune signaling systems.